TV 맛집 프로그램의 정보특성이 외식소비자의 감정이입과 태도, 방문의도에 미치는 영향 연구 - 이진(Jin Lee); 윤효실(Hyo Sil Yoon); 윤혜현(Hye Hyun Yoon) (東아시아食生活學會誌, 2017)
Recently, many TV restaurant programs become popular, and TV restaurant programs have a big impact on Korean restaurant consumers. The purpose of this study was to understand the effects of information attributes in Korean TV restaurant review programs food service customer's empathy, attitudes and visit intention. Based on a total of 254 samples obtained from the empirical research, this study reviewed the reliability and fitness of the research model using the Amos program. The hypothesized relationships in the model were tested simultaneously by using structural equation model (SEM). SEM showed that the beneficialness (${β}=.187$, p<.01), amusement (${β}=.427$, p<.001) and vividness (${β}=.243$, p<.01) showed positive significant effects on customer's empathy. Customer's empathy had a positive significant effect on attitudes (${β}=.645$, p<.001) and visit intentions (${β}=.157$, p<.001). The information attributes of TV restaurant programs and the causal relationship between empathy of consumers were examined. We also verified that empathy positively affects attitudes toward intentions to visit restaurants introduced on TV restaurant programs. Limitations and future research directions are also discussed.